Arctic foxes [book with audioplayer] - Pettiford, Rebecca (Blastoff! readers. Animals of the Arctic., 2019)
"Relevant images match informative text in this introduction to Arctic foxes. Intended for students in kindergarten through third grade"--Provided by publisher